Analysis of the Role of Value Congruence, Partnerships with External Parties on Sustainable Development Moderated by the Effectiveness of CSR Program Integration in South Sulawesi Province - Siswan, Siswan; Hasniaty, Hasniaty; Suyuthi, Nurmadhani Fitri (Universitas Negeri Makassar, 2024)
This research aims to analyze the influence of the role of value congruence, partnerships with external parties on sustainable development. Apart from that, this research also analyzes how the variable role of CSR program integration effectiveness mediates the role of value congruence and partnerships with external parties. The research methodology is a correlational quantitative approach which aims to understand and explain the phenomenon of CSR programs in South Sulawesi Province in depth. Data analysis uses descriptive statistics and inferential statisticsusing the SPSS program. The testing technique uses path analysis and Sobel test. The research results show that 1) the role of value congruence (path coefficient value 0.0332) has a positive and significant effect on the effectiveness of CSR program integration, 2) partnerships with external parties (path coefficient value 0.315) has a positive and significant effect on the effectiveness of CSR program integration, 3 ) the role of value conformity (path coefficient value 0.477) has a positive and significant effect on sustainable development, 4) partnerships with external parties (path coefficient value 0.194) has a positive and significant effect on sustainable development, 5) effectiveness of CSR program integration (path coefficient value 0.424) positive and significant effect on sustainable development, 6)the role of value congruence does not have a significant positive effect on sustainable development through the effectiveness of CSR program integration (Sobel test value 1.1615 < 1.96) and 7) partnerships with external parties have a positive and significant effect on sustainable development through the effectiveness of CSR program integration (Sobel Test Value 2.574 > 0.194).